Sistem Penyiraman Tanaman Otomatis Berbasis Mikrokontroler Di Balai Pembenihan Tanaman IP2TP Kabupaten Sigi - Moh.Murdani Moh.Murdani; Suparman Suparman; Hariyadi Darmawan (Sekolah Tinggi Manajemen Informatika dan Komputer (STIMIK) Bina Mulia Palu, 2025)
The development of increasingly advanced technology encourages the birth of innovations to make human work easier, one of which is in the field of agriculture. Manual watering of plants is considered inefficient because it takes time, effort, and often does not meet the water needs of plants. This research aims to design and implement an automatic plant watering system based on the NodeMCU ESP8266 microcontroller by utilizing a soil moisture sensor (Soil Moisture Sensor) as a moisture condition detector. If the soil moisture is below the threshold, the microcontroller will activate the relay to turn on the water pump automatically, while if the soil is still moist the pump will stop working. This study uses a prototyping method with black-box testing. The research data was obtained through observation at the IP2TP Plant Hatchery Center in Sigi Regency, interviews with employees, and literature studies from related literature. The results of the study show that the system is able to function as designed, namely reading the soil moisture conditions in real-time, controlling the water pump, and displaying the status on the LCD. Thus, this system is proven to help farmers in improving the time efficiency and effectiveness of watering crops.